PENGARUH HARGA, KUALITAS PRODUK, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN STUDI KASUS PADA USAHA RUJAK CINGUR WARUNG CAK NO GEDUNG TVRI DI KOTA SURABAYA - Ilfi Sakinah, Sherin (GEMAH RIPAH: Jurnal Bisnis, 2022)
Lately, there are many culinary businesses that are favored by young people or the millennial generation, ranging from traditional food to contemporary food. The millennial generation is currently competing to taste various types of culinary that are popular among them, the millennial generation tends to enjoy and create content on the social media they use. To be able to attract customers’ buying interest, entrepreneurs must strive to improve and maintain product quality and promotions at appropriate selling prices, and become able to answer consumer needs and desires. This study aims to determine the effect of price, product quality, and promotion on purchasing decisions for the rujak cingur at Cak No TVRI building in Surabaya City. The population in this study are consumers who have purchased rujak cingur Cak No. TVRI products in Surabaya City. By using purposive sampling technique, data collection of respondents using a questionnaire as many as 103 respondents. The analysis used in this research is multiple linear regression, F test, t test, correlation test, coefficient of determination test. The results of this study indicate that price, product quality, and promotion have an effect on purchasing decisions.